Directed designs the covers of children's magazines methods (Al-Academy, 2017)
The design processes in general and the design system in particular need to be studied and knowledge. Based on this vision, we find the need for constant research on the design processes, and the subject of the techniques of the designs of the covers of children magazines did not have the view of the researchers to make them the subject of study, For the subject of this research, the problem of research is determined according to the following question:- What are the methods used in designing children magazine covers in Iraq?Through this research we seek to find solutions to this question as well as it will serve the cognitive side of a modern study and development of a broader understanding of the subject. Through four chapters, the first chapter included the problem of research and the need for it, and then the importance of research and identified by the following points:Developing the technical skills of the designers of magazine covers for children especially those working in the Children's Culture House in Iraq.To develop the scientific, intellectual and cultural knowledge of children's magazine designers, especially in the field of print design.This was followed by the research objective, which is determined by: Identifying the methods of the design of magazine covers of children magazines (magazine).Then search limits:Objective (material) / means to study (methods of producing designs of children magazine covers).The spatial limit / magazine (مجلتي) issued by the House of Culture of Children, affiliated to the Iraqi Ministry of Culture.Time limit / magazines issued in 2015.The researcher then defined the terms related to the research, which are considered as the foundations adopted in the literature of specialization and there were the following terms: methods, output.Hence, the second chapter includes the theoretical framework of two subjects.- Magazine cover design techniques.- Journal between design and output technology.- Methods of producing the magazine.The second section includes:- System and organization.- Concept of output.- Foundations and elements in the design structure of children's magazines.- Structural elements of magazine cover design.Then theoretical framework indicators, represent a scientific summary of the literature of the theoretical material.